Assessment of the Performance for a Hybrid PV / Solar Chimney - Sabah Hussein, Abdullah; Khalil Ahmed, Omer (International Journal of Engineering and Technology, 2018)
In this study, we assessed the performance of a new design of the solar chimney by merging the collector through integrated solar panel by using a solar cell as a glass roof. Assessment of the performance of this new design is the main purpose of this study. Experimental work conducted at Kirkuk (35.46 oN, 44.39 oE) northern Iraq. The experiments conducted during the summer season. A hybrid solar chimney consisting of a solar panel cover replaces the glass cover in the conventional solar chimney. Different instruments used to measure temperature, air velocity, electric current and voltage of solar panel. An experimental model was built to anticipate the performance of a hybrid chimney.It has been shown, that there is an increase in the temperature of the PV panel from the beginning of the day with increased of the incident solar radiation values. It is observed that the angle (45) is the best angle for the energy production. Also, it is noted that (45-panel angle) gives the highest efficiency to this system of the three angles that have been measured (30Â°, 35Â°, 45Â°). The results showed the efficiency of the PV/ solar chimney ranges from 8 % to 13 %. The maximum rise of the air temperature in the solar collector it is found to be 2â€“3 oC on a typical day.Â Â